Pengaruh Implementasi Internal Control Over Financial Reporting (ICoFR) dan Peran Komite Audit terhadap Kualitas Audit di Sektor Jasa Keuangan Indonesia - Puri, Dwi Mareta; Andani, Reiva; Kristianto, Giovanny Bangun (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
This study investigates the influence of Internal Control over Financial Reporting (ICoFR) implementation and the role of the audit committee on audit quality in Indonesia’s financial services sector. The research is motivated by cases such as Jiwasraya, Asabri, and Garuda Indonesia, which revealed weaknesses in internal control and audit oversight despite strict regulations by the Financial Services Authority (OJK). Grounded in agency theory, the study assumes that effective ICoFR reduces information asymmetry by ensuring reliable financial reporting, while the audit committee serves as a governance mechanism to monitor internal control and support external auditors. Using a quantitative, explanatory approach, data were collected through questionnaires distributed to internal auditors, external auditors, and audit committee members in financial service companies listed on the Indonesia Stock Exchange. Variables were measured based on COSO framework indicators for ICoFR, independence and competence for audit committees, and independence, compliance, and reliability for audit quality. Data analysis employed validity and reliability testing, regression, and SEM-PLS. Results show that ICoFR (β = 0.39; p < 0.001) and the audit committee (β = 0.36; p < 0.001) have significant positive effects on audit quality. Together, both factors explain 53% of the variance in audit quality (R² = 0.53). These findings confirm agency theory and emphasize that substantive, rather than merely formal, compliance with governance regulations is crucial to enhancing audit quality.